Chile in Joseph R. Biden’s foreign policy doctrine: problems and prospects - Roman Romanov (Латиноамериканский исторический альманах, 2022)
Chile is one of the most developed countries in Western hemisphere. It has a high economic potential and a comparatively stable political sys-tem. Election of a new president will not only influence domestic af-fairs but also affect Santiago’s relations with main global actors, first and foremost, with the United States. After the end of Cold War Wash-ington utilized its resources in Eurasia which generated a leadership vacuum in Latin America. The US positions in the region were weak-ened during Trump’s presidency. The latter did not only fail to propose an alternative path of interregional development but used rhetoric of ul-timatums towards Latin-American countries. Renewal of relations with regional powers is one of the main goals of the Biden administration. Cooperation with Chile could optimize White House’s prospects not only in restoration of its regional influence but in the context of the great power competition. Economic development and solid institutions may make Santiago effectively contain China’s influence in the region. A new “Pink tide” will deepen Sino-American rivalry in Latin America and force the United States to widen its policy-toolkit.Partnership is relevant in several spheres: economic, strategic and cultural. The latter two are easier to realize because presidents’ capacity lets them simplify implementation of projects from those fields notwithstanding absence of legislative power’s support. Nevertheless, international context char-acterized by conflict in Ukraine and economic instability does not allow Washington to work out a long-term and efficient strategy towards Lat-in America in general and Chile in particular.